Manifesto politik, rancangan dasar dan struktur - Partai Uni Demokrasi Indonesia (Jakarta : Partai Uni Demokrasi Indonesia, 1996)
Political manifest and by-laws of Partai Unit Demokrasi Founded May 29, 1995; Intended as an oppositional party
Keywords: Partai Uni Demokrasi Indonesia -- By-laws; Indonesia -- Politics and government -- 1966-1998